Oral contraceptives in gall stone diseases - Khan, MK; Jalil, MA; Khan, MS (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S40-45 The abstract of this article is available on the PubMed website